Neurological manifestations of the Mendelian‐inherited autoinflammatory syndromes - SANCHEZ, GINA A MONTEALEGRE; HASHKES, PHILIP J (Developmental medicine and child neurology, 2009)
Autoinflammatory syndromes include an expanding list of conditions characterized by unprovoked recurrent attacks of systemic inflammation with lack of auto‐antibodies or autoreactive T cells. Many of these syndromes are genetic diseases with a Mendelian inheritance. Neurological manifestations may be one of the major clinical features and, in some cases, the presenting symptom of these syndromes. The purpose of this review is to increase the recognition among neurologists of the Mendelian‐inherited autoinflammatory syndromes by highlighting the neurological manifestations in the context of other symptoms that should lead physicians to suspect these syndromes. Most important for neurologists are the cryopyrin‐associated periodic syndromes that include familial cold autoinflammatory syndrome, Muckle–Wells syndrome and neonatal‐onset multisystem inflammatory disease (called chronic infantile neurological cutaneous and articular syndrome in Europe). We also review other syndromes with less common neurological involvement, including familial Mediterranean fever, tumor necrosis factor receptor‐associated periodic syndrome, and hyperimmunoglobulinemia D syndrome. Because these syndromes are often treatable and irreversible damage is prevented if they are treated early, it is important to recognize the features that may result in these syndromes presenting to a neurologist, especially in early childhood.